The Impact of Narrative Method Used to Improve Some Skills of Reading Aloud Related to 5th Grade Students in Medina Area - Aljuhani, Muhammad Saeed (Journal of Curriculum and Teaching Methodology, 2023)
The purpose of the study is to investigate the impact of using the narrative method in improving the skills of performance loud reading (Spell accuracy, Language control, stops, presenting the meaning). To achieve this aim the researcher developed a test based on observation. Moreover, some reading texts were rephrased from the reading book of the 5th grade in Saudi Arabia.The sample of the study consisted of (43) male students from the 5th grade in Medina area distributed on two classes in Imam Hafs Bin Suleiman school in Median Educational directorate in the schooling year 2010/2011 chosen purposefully, classes were divided into a control group totaling (21) male students studied through the traditional method and an experimental group totaling (22) male students studied through the narrative method. Quasi experimental approach was used by administrating pre and post test on both groups.The findings of the study showed that there were significant statistical differences at the level of (α = 0.05) between the means of loud reading due to the teaching method for the favor of the experimental group (Narrative method).Based on the findings of the study the researcher recommended the use of the narrative method to develop loud reading skills among basic stage students.
Keywords: Narrative Reading; Speaking skills; the line 5; Kingdom of Saudi Arabia